Comparative Analysis of Formats and Readability of Articles published in a News Paper and A Farm Magazine - V. Suresh; J. Vasanthkumar (Journal of Agricultural Extension Management, 2025)
In India there are several media disseminating the recent agricultural technologies to farmers. Among them, print media play a vital role in disseminating the recent technologies to literate farmers. Agricultural Journalism in India came into existence just five decades ago. It is now gaining importance, particularly after the establishment of State Agricultural Universities (SAUs), the technical information needs to be provided to the farmers at the right time in a right way, so that the productivity can be increased